PENGARUH BUDAYA INDIVIDUAL DAN PENGEMBANGAN PROFESIONAL AUDITOR TERHADAP KUALITAS AUDIT PEMERINTAH DENGAN EFIKASI DIRI SEBAGAI VARIABEL MEDIASI (STUDI PADA AUDITOR BPKP KALIMANTAN BARAT) - B2091172006, Meidina Siti Soraya (MAKSI UNTAN, 2020)
The research aims to determine the effect of the individual culture and professional development auditor on audit quality with self-efficacy as a mediator. Specifically, researchers examine the mediating effects of self-efficacy on the relationship between individualism culture and professional development with audit quality. Social cognitive theory and self-efficacy are used as theoretical frameworks. The study used purposive sampling of 33 auditors in the selected sample, BPKP West Kalimantan. Data analysis techniques using WarpPLS 6.0.The results showed that self-efficacy had a significant impact on audit quality. In addition, there is a significant effect of mediating self-efficacy on the relationship between professional development and audit quality. Meanwhile, there is no significant effect of mediating self-efficacy on individual cultural relationships and audit quality is not significant. Which means that internal auditors at BPKP West Kalimantan have a high level of self-motivation and self-development in improving audit quality.Keywords: Self-efficacy, Social Cognitive Theory, Individual Culture, Professional Development, Audit QualityDAFTAR PUSTAKA Akhtar, M. (2019). What is Self-Efficacy? Bandura’s 4 Sources of Efficacy Beliefs. Positive Psychology, http://positivepsychology.org.uk/self-efficacy-definition-bandura-meaning/.American Psychological Association. (2019). Teaching Tip Sheet: Self-Efficacy. https://www.apa.org/pi/aids/resources/education/self-efficacy.Bandura, A. (1977). Self-efficacy: Toward a unifying theory of behavioral change. Psychological Review, 84(2), 191-215.Bandura, A. (1989). Social Cognitive Theory. In R. Vasta (Ed.), Annals of child development. Vol. 6. Six theories of child development (pp. 1-60). Greenwich, CT: JAI Press.Chadegani, A. A., Zakiah, M. M. & Iskandar, T. M. (2015). The Influence of Individual Characteristics on Auditors’ Intention to Report Errors. Journal of Economics, Business and Management, Vol. 3, No. 7.Columbia University of New York. (2019). Finance Gateaway Internal Audit. https://finance.columbia.edu/content/types-audits.Erlina & Muda, I. (2018). The Effect of Self Efficacy and Professional Development on The Work Quality of Internal Auditor. International Journal of Civil Engineering and Technology (IJCIET), Vol. 9, Issue 5.Knock, Ned. (2015). WarpPLS 5.0 User Manual. ScriptWarp Systems Laredo, Texas USA.Kustinah, S. (2013). The Influence of Dysfunctional Behavior and Individual Culture on Audit Quality. International Journal of Scientific & Technology Research Vol. 2, ISSN 2277-8616.Mahdi, S. AR. (2015). Analisis faktor-faktor Penentu Kualitas Audit dengan Moral Judgment sebagai Pemoderasi (Studi pada BPK RI Perwakilan Provinsi Maluku Utara). Jurnal Universitas Khairun Ternate.Salih K, W. & Hla, D, T. (2016). Impact of Organizational Culture to Improve Audit Quality Assurance in the Public Sector. Journal of Business and Management, PP 121-124.Shue C, L., Jau M, S. & Sang B, T. (2016). A Comprehensive Survey of Government Auditors’ Self-efficacy and Professional Development for Improving Audit Quality. Jurnal SpringerPlus, 5:1263.Suratno., Djaddang, S., Astuti S, B. & Supriatno, B. (2016). The Role of Self-Efficacy of The Professionalism of Accountants, Auditors Individual Cultural Relations with Government Quality Investigative Audit (Study on Auditor BPK Government in Jakarta). Jurnal ICEEBF, 2540-7481.Tuanakotta, Theodorus M. (2007). Akuntansi Forensik dan Audit Investigatif. Jakarta, Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.